4D Metamaterials with Zero Poisson's Ratio, Shape Recovery, and Energy Absorption Features. Issue 9 (5th July 2022) - Hamzehei, Ramin; Serjouei, Ahmad; Wu, Nan; Zolfagharian, Ali; Bodaghi, Mahdi
Abstract : This article introduces novel 3D zero Poisson's ratio (ZPR) metamaterials for reversible energy absorption applications fabricated by 4D printing technology. The designs are introduced based on piecemeal energy absorption (PEA) and conventional energy absorption (CEA) approaches. Topologically, the design of the 3D metamaterials is founded on star‐shaped unit cells herein. To achieve the PEA behavior, horizontal bars are merged into the parent star‐shaped unit cell. This leads to introducing multistiffness unit cells (controllable unit‐cell densifications) to provide stability and different peak force levels during compression. For further evaluation, finite element analysis (FEA) is employed. To illustrate the design functions during physical operation and validate the FEA, lattice‐based metamaterials are fabricated from resin with a shape recovery property by an SLA 3D printer and tested mechanically. Close coincidence is observed between the FEA and the experiments, showing the accuracy of the modeling. A thermal test, via a heating–cooling process, is also carried out to display the shape recovery capability of metamaterials where plastic deformations are fully released, and samples get back to their original shapes. Finally, the newly proposed ZPRs are compared with conventional 3D reentrant metamaterials in terms of energy absorption capacity, demonstrating their considerable mechanical performances. Abstract : High‐performance 4D metamaterials are introduced for reversible energy absorption applications fabricated by SLA 3D printing technology. The designs introduce multistiffness unit cells and are drawn based on piecemeal and conventional energy absorption criteria (PEA and CEA). The energy absorption capacity of the newly designed metamaterial enhances up to 267% compared to conventional 3D reentrant metamaterials.